(untitled) (Progress Annals: Journal of Progressive Research, 2024)
This article explores the role of government financial policy in driving economic growth, with a specific focus on Uzbekistan’s efforts in recent years. It examines key financial instruments such as taxation reforms, public investments, and subsidies, highlighting how they contribute to enhancing business investment, improving productivity, and fostering innovation. Through analysis of Uzbekistan’s tax reforms, public spending on infrastructure, and agricultural subsidies, the article provides insights into the broader impacts of these policies on the nation’s economic stability and long-term growth. Additionally, it draws comparisons to practices in other countries, offering a comprehensive view of the challenges and opportunities in implementing effective financial policies